The role of infrastructure and government policies in determining the efficiency of Kenya's maize marketing system in the post-liberalization era - Karugia, Joseph T.; Wambugu, Stephen K.; Oluoch-Kosura, Willis (International Food Policy Research Institute, 2004)
Although Kenya has liberalized its agricultural market, it continues to experience frequent food shortages that greatly compromise the welfare of its citizens, especially the poor. In Kenya food shortages are synonymous with maize shortages. Persistent maize crises sometimes manifest themselves in simultaneous existence of grain surpluses in some regions and grain shortages in others. This situation has placed great doubt on the efficiency of the Kenyan food marketing system.